On Colonial Past and Present in Sápmi: Considering Ideas of the Land of the Future in Northern Sweden - Össbo, Åsa (Journal of Northern Studies, 2025)
Ever since the 1630s and the discovery of silver ore deposits in the alpine areas of Sápmi, Sweden has nurtured settler colonial ideas in relation to Sápmi and the Sami. The first legal settler colonial tool was the Lappmark Proclamation of 1673. However, the vision of “the land of the future” with mining and agriculture proved to be somewhat of a mirage. A second wave of settler colonial ideas came with the industrial breakthrough. As we are now entering the third era of settler colonial ideas, sacrificing Sami lands, rights, and self-determination seems to be a continued strategy of the Swedish state. Once again, entrepreneurs, companies and politicians project the idea of a “land of the future” onto the north and Sápmi. In this article, I describe this phenomenon, which has been—and still is—based on settler colonial ideas, anopticism and sidelining of the Sami and their historical as well as current land rights.